2016
DOI: 10.1111/1365-2656.12495
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural flexibility in migratory behaviour in a long‐lived large herbivore

Abstract: Migratory animals are predicted to enhance lifetime fitness by obtaining higher quality forage and/or reducing predation risk compared to non-migratory conspecifics. Despite evidence for behavioural flexibility in other taxa, previous research on large mammals has often assumed that migratory behaviour is a fixed behavioural trait. Migratory behaviour may be plastic for many species, although few studies have tested for individual-level flexibility using long-term monitoring of marked individuals, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
248
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(261 citation statements)
references
References 69 publications
6
248
1
Order By: Relevance
“…We also evaluated the influence of age and reproductive status on switching behaviour and fidelity, because they are individually variable traits (Eggeman et al, 2016) and are expected to change depending upon state of the animal (Jachowski & Singh, 2015;Monteith et al, 2011;Mysterud et al, 2011;Singh et al, 2012). Upon initial capture for 142 animals in six of the study populations, we extracted the incisiform TA B L E 1 Study duration, sample sizes for animal and migration sequences, and monitoring duration of GPS-collared mule deer in nine study populations across the Intermountain West, USA canine using standardized methods to facilitate ageing via cementum annuli (Bleich et al, 2003;Swift et al, 2002).…”
Section: Migration Fidelity Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…We also evaluated the influence of age and reproductive status on switching behaviour and fidelity, because they are individually variable traits (Eggeman et al, 2016) and are expected to change depending upon state of the animal (Jachowski & Singh, 2015;Monteith et al, 2011;Mysterud et al, 2011;Singh et al, 2012). Upon initial capture for 142 animals in six of the study populations, we extracted the incisiform TA B L E 1 Study duration, sample sizes for animal and migration sequences, and monitoring duration of GPS-collared mule deer in nine study populations across the Intermountain West, USA canine using standardized methods to facilitate ageing via cementum annuli (Bleich et al, 2003;Swift et al, 2002).…”
Section: Migration Fidelity Analysismentioning
confidence: 99%
“…The decision of whether to migrate often refers to facultative migration or "switching" behaviour, where animals may migrate one year, but not the next. However, several recent studies that monitored individual animals for multiple years have shown varying degrees of switching behaviour, including impala (Aepyceros melampus) (Gaidet & Lecomte, 2013), moose (Alces alces) (White, Barten, Crouse, & Crouse, 2014), roe deer (Capreolus capreolus) (Cagnacci et al, 2011;Gurarie et al, 2017;Peters et al, 2017), white-tailed deer (Odocoileus hemionus) (Fieberg, Kuehn, & Delgiudice, 2008;Sabine et al, 2002), red deer (Cervus elaphus) (Martin et al, 2018;Mysterud et al, 2011) and North American elk (Cervus canadensis) (Eggeman et al, 2016;Hebblewhite & Merrill, 2011). However, several recent studies that monitored individual animals for multiple years have shown varying degrees of switching behaviour, including impala (Aepyceros melampus) (Gaidet & Lecomte, 2013), moose (Alces alces) (White, Barten, Crouse, & Crouse, 2014), roe deer (Capreolus capreolus) (Cagnacci et al, 2011;Gurarie et al, 2017;Peters et al, 2017), white-tailed deer (Odocoileus hemionus) (Fieberg, Kuehn, & Delgiudice, 2008;Sabine et al, 2002), red deer (Cervus elaphus) (Martin et al, 2018;Mysterud et al, 2011) and North American elk (Cervus canadensis) (Eggeman et al, 2016;Hebblewhite & Merrill, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1)48. Net squared displacement has been successfully used to estimate the migration timing and summer range of migratory ungulates tracked by GPS transmitters4950. We used the R function identify to determine the start and end locations of the net squared displacement plateau.…”
Section: Methodsmentioning
confidence: 99%